Distribution of citrate utilization plasmids in Salmonella strains of bovine origin in Japan. - Ishiguro, N (1980)
Attempts to detect transferable citrate-utilizing (Cit) ability in enterobacterial strains were carried out by conjugation experiments. Of 318 strains of Salmonella typhimurium and 1 strain of Salmonella bredeney isolated from cattle in Japan from 1970 to 1979, 107 (33.5%) strains contained transferable Cit characters. Most of the strains transferred the Cit characters to recipient Escherichia coli more efficiently at 28 degrees C than at 37 degrees C, indicating that their transfer of the Cit character is thermosensitive. Transferred Cit characters were found in association with drug resistance markers such as ampicillin, chloramphenicol, kanamycin, streptomycin, sulfonamides, and tetracycline or with mercury resistance, but Cit plasmids conferring Cit ability alone were also obtained. Of 221 conjugative Cit plasmids tested for fertility inhibition (Fi), all but 2 were Fi- and exhibited thermosensitive transfer; 2 Cit plasmids showing the Fi+ character were also isolated from 2 S. typhimurium strains. No transferable Cit character was detected from strains of Proteus, Serratia, Klebsiella, Enterobacter, and Citrobacter spp. isolated from humans or cows in the present study. The utilization of tricarboxylic acids by strains with plasmid-borne Cit ability was examined, and two different patterns of utilization were found in the Cit+ E. coli transconjugants.